Sistem Persamaan Linear Dua Variabel dengan Metode Subsitusi dan Eliminasi - Layli Maydawati (Jurnal Pustaka Cendekia Pendidikan, 2024)
System of Linear Equations of Two Variables with substitution and elimination methods is one of the sciences studied in Linear Algebra. Systems of Linear Equations learn how to solve engineering problems and solve solutions to problems using Linear Algebra. Problems that often arise in finding solutions to systems of linear equations are usually related to terms in equations in the form of fractions. So we need the right method to solve the problem. There are two ways to solve this problem and there are also examples of its application in everyday life. The system of two-variable linear equations (SPLDV) is one of the main subjects taught in class VIII mathematics learning. By studying SPLDV material, students are expected to be able to: identify and associate problems in everyday life with the SPLDV concept, implement the SPLDV concept in solving related life problems, and use various ways to solve SPLDV.